Evaluasi Penambahan Rimpang Temu Putih (Curcuma zedoaria) dan Jahe Gajah (Zingiber officinale var. officinale) dalam Bentuk Enkapsulasi dan Non Enkapsulasi Terhadap Penampilan Produksi Ayam Pedaging - Rohma, Laila Nur; Wijayanti, Desna Ayu (Bantara Journal of Animal Science, 2023)
AbstractThis study aimed to evaluate and examine the content of the essential oils of white turmeric and giant ginger, how the effect of phytobiotic forms (encapsulation and non-encapsulation), and the usage level influence broiler production. The research material in the phase included 196 DOC of broiler, basal feed, and phytobiotic encapsulation and non-encapsulation. The in vivo study was divided into seven treatments with four replications, the experimental design used was a completely randomized design (CRD), and the statistical analysis used was variance analysis (ANOVA), which, if the data showed significant differences, then continued with Orthogonal Contrast Test and Duncan's Multiple Range Test. The treatments given were basal feed (P0), basal feed plus white turmeric and giant ginger in the form of non-encapsulation 0.6 (P1), 0. 8 (P2), 1% (P3), and basal feed plus white turmeric and giant ginger in the form of encapsulation 0.6 (P4), 0.8 (P5) and 1% (P6). The results showed that the treatment also significantly affected (P<0.05) feed consumption, body weight gain, Income Over Feed Cost, and crypt depth. However, the treatment did not significantly affect feed conversion (P> 0.05). Overall, the treatment of P6, a mixture of white turmeric and giant ginger in encapsulation with a level of 1%, is the best. The treatment did not significantly affect feed conversion (P> 0.05). Overall, the treatment of P6, a mixture of white turmeric and giant ginger in encapsulation with a level of 1%, is the best. The treatment did not significantly affect feed conversion (P> 0.05). Overall, the treatment of P6, which is a mixture of white turmeric and giant ginger in the form of encapsulation with a level of 1% is the best treatment. Keywords : broiler, encapsulation, giant ginger, phytobiotic and performance, white turmeric